HAWAIIAN SKIRT, and F-box gene from Arabidopsis, is a new player in the microRNA pathway - Zhang, Xuebin; Jayaweera, Dasuni; Peters, Janny L.; Szecsi, Judit; Bendahmane, Mohammed; Roberts, Jeremy A.; González-Carranza, Zinnia H. (2018)
F-box proteins belong to a multi-protein E3 ubiquitin ligase complex (SCF) that target proteins for degradation via the proteasome.We demonstrated that HAWAIIAN SKIRT(HWS), an Arabidopsis ubiquitin protein ligase (SCFHWS), regulates organ growth, flower development and timing of abscission. Mutants of this gene (hws-1) are pleiotropic and the most obvious phenotype is the fusion of its floral organs, a phenotype shared with the cuc1/cuc2 double mutants and over-expressing lines of MIR164B. To understand the molecular mechanisms of HWS during plant development, an ethylmethylsulphonate mutagenized population of hws-1 seeds was generated and screened for mutations suppressing the hws-1 sepal fusion. We isolated shs-1/hws-1, shs-2/hws-1, and shs-3/hws-1, (suppressor of hws-1) mutants. Mapping analyses shown that shs1 is mutated in the miRNA164 binding site of CUPSHAPED COTYLEDON1 (CUC1) mRNA; while shs-2 and shs-3 are novel alleles of the plant homolog of Exporting-5 HASTY (HST), known to be important in miRNA biogenesis, function and transport. Consequently, we renamed them cuc1-1D, hst23 and hst24, respectively. We demonstrated that transcript levels of CUC1 and CUPSHAPED COTYLEDON 2 (CUC2), and MIR164 change in cuc1-1D and in hws-1 mutants; analyses revealed a role for HWS in cell proliferation and control of floral organ number. Additional genetic crosses between hws-1 and mutant lines for genes in the miRNA pathway were performed and double mutants obtained shown restoration of the hws-1 sepal fusion phenotype. Our data propose HWS as a new regulator in miRNA pathway and reveal a role for HWS to control floral organ number and cell proliferation.